Method of Prospective Diagnosis of Weak Signals of Potential Phenomena by Types of Company Activity Метод перспективной диагностики слабых сигналов потенциальных явлений по видам деятельности предприятия - Kuzmin Oleg Ye.; Adamiv Marta Ye. (Bìznes Inform, 2013)
Modern uncertain and hardly predictable conditions of activity call for taking into account weak signals, which inform about appearance of potential phenomena of the functioning environment in the process of management activity of a company on the basis of probabilistic assessment. With that aim in mind a method of prospective diagnosis of weak signals of possible changes by types of company activity was developed. This method allows diagnosing a specific potential phenomenon by original weak signals from the position of its most probable appearance in a future period. Realisation of this method forms possibilities for increase of the level of preparation of a company for potential changes of conditions of its activity. В современных неопределенных и малопрогнозируемых условиях деятельности возникает необходимость учета слабых сигналов, которые на вероятностных основах сообщают о возникновении потенциальных явлений среды функционирования в процессе управленческой деятельности предприятия. С этой целью разработан метод перспективной диагностики слабых сигналов возможных изменений по видам деятельности предприятия, позволяющий диагностировать конкретное потенциальное явление по исходным слабым сигналом с позиции его наиболее вероятного возникновения в будущем периоде. Реализация этого метода формирует возможности для повышения уровня подготовки предприятий к потенциальным изменениям условий деятельности.